Knowledge of blood-borne infectious diseases and the practice of universal precautions amongst health-care workers in a tertiary hospital in Malaysia - Abd Hamid, Mohd Zaini; Abd Aziz, Noorazah; Abdul Rahman, Anita; Othman, Norlijah (Southeast Asian Ministers of Education Organisation, 2010)

(untitled)
This study aimed to assess the knowledge of blood-borne diseases transmitted through needle stick injuries amongst health-care workers in a tertiary teaching hospital. We also aimed to assess the practices of universal precautions amongst these workers and its correlation with the facts. We carried out a cross-sectional study from January to July 2008 involving various levels of health-care workers in Serdang Hospital, Selangor, Malaysia. A self-administered questionnaire assessing knowledge of blood-borne diseases and universal precautions, and actual practice of universal precautions was used. Two hundred fifteen respondents participated in this study; 63.3% were staff nurses. The mean knowledge score was 31.84 (SD 4.30) and the mean universal practice score was 9.0 (SD 2.1). There was a small, positive correlation between knowledge and actual practice of universal precautions (r = 0.300, n = 206, p < 0.001) amongst the cohort studied. Factors such as age and years of experience did not contribute towards acquisition of knowledge about blood-borne illnesses or the practice of universal precautions.